1995
DOI: 10.1073/pnas.92.18.8239
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the distance between two spin labels attached to a macromolecule.

Abstract: An EPR "spectroscopic ruler" was developed using a series of a-helical polypeptides, each modified with two nitroxide spin labels. The EPR line broadening due to electron-electron dipolar interactions in the frozen state was determined using the Fourier deconvolution method. These dipolar spectra were then used to estimate the distances between the two nitroxides separated by 8-25 A. Results agreed well with a simple a-helical model. The standard deviation from the model system was 0.9 A in the range of [8][9]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
450
2
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 398 publications
(469 citation statements)
references
References 27 publications
14
450
2
1
Order By: Relevance
“…The gel shift assays indicated that spin-labeled RRE and Rev form a specific complex, so we expected to see a broadening of the spectra due to the motional constraints placed on the spin label when Rev was added to the RRE constructs+ Indeed, broadening upon complex formation is clearly visible in Figure 3 as an increased broadening for RRE plus unlabeled Rev (dotted line)+ Additional broadening is seen in RRE plus labeled Rev (solid line) due to dipolar interactions, which we examined in detail at low temperatures (see below)+ The broadening due to complex formation was also observed for RRE2 and RRE3 (data not shown); however, the additional broadening due to dipolar interactions was not seen in RRE3, consistent with the separation (.25 Å) of the two probes predicted by the NMR structure (Rabenstein & Shin, 1995)+ The relative spectral broadening diminished when Rev was added in more than, or less than, the optimal ratio of 1:1 (data not shown)+ The peaks became less broad due to the presence of free Rev or RRE+ Ultimately, we are interested in using this new technique to find distances within complexed RNA structures and obtain information about RNA function+ To FIGURE 3. Room-temperature EPR absorption spectra of bound and unbound Rev and RRE1+ All spectra were taken at 22 8C in a Bruker ESP300 EPR spectrometer with a modulation amplitude of 0+5 G+ The broadening in the bound and singly labeled systems is due to decreased nitroxide mobility+ Additional broadening in the bound and doubly labeled system is due to spin-spin dipolar interactions+ measure distances between the spin labels in the RRERev complexes, EPR spectra were collected at Ϫ140 8C+ These absorption spectra are shown overlapped in Figure 4+ The spectrum for RRE2-Rev is the broadest, followed closely by RRE1-Rev and RRE3-Rev+ At low temperatures at which the molecular motion is completely frozen, the broadening of EPR spectra is exclusively due to dipole-dipole interactions between the two spin labels (Rabenstein & Shin, 1995)+ For labels that are proximal and more interacting, spectra are broader+ Conversely, distant spin labels yield narrower peaks+ Qualitatively, then, it is clear that the distance between labels in the RRE3-Rev complex is greater than that in either the RRE1 or RRE2 complexes+ Quantitatively, the overall spectral broadening, due to the splitting of EPR lines resulting from spin dipolar interactions, depends on the inverse cube of the distance (r ) between the spins+ This is given by the equation 2B ϭ 1+5g e b(3 cos 3 u Ϫ 1)/r 3 where 2B is the splitting due to the spin-spin interactions, g e is the isotropic g value of an electron, b is the electron Bohr magneton, and u is the angle between the interspin vector and the external magnetic field, which, for a frozen molecule, is fixed in time and is isotropically distributed+ The magnitude of B is obtained from a Fourier analysis of a frozen EPR spectrum, a method developed by Rabenstein and Shin (1995)+…”
Section: Epr Spectroscopysupporting
confidence: 65%
See 4 more Smart Citations
“…The gel shift assays indicated that spin-labeled RRE and Rev form a specific complex, so we expected to see a broadening of the spectra due to the motional constraints placed on the spin label when Rev was added to the RRE constructs+ Indeed, broadening upon complex formation is clearly visible in Figure 3 as an increased broadening for RRE plus unlabeled Rev (dotted line)+ Additional broadening is seen in RRE plus labeled Rev (solid line) due to dipolar interactions, which we examined in detail at low temperatures (see below)+ The broadening due to complex formation was also observed for RRE2 and RRE3 (data not shown); however, the additional broadening due to dipolar interactions was not seen in RRE3, consistent with the separation (.25 Å) of the two probes predicted by the NMR structure (Rabenstein & Shin, 1995)+ The relative spectral broadening diminished when Rev was added in more than, or less than, the optimal ratio of 1:1 (data not shown)+ The peaks became less broad due to the presence of free Rev or RRE+ Ultimately, we are interested in using this new technique to find distances within complexed RNA structures and obtain information about RNA function+ To FIGURE 3. Room-temperature EPR absorption spectra of bound and unbound Rev and RRE1+ All spectra were taken at 22 8C in a Bruker ESP300 EPR spectrometer with a modulation amplitude of 0+5 G+ The broadening in the bound and singly labeled systems is due to decreased nitroxide mobility+ Additional broadening in the bound and doubly labeled system is due to spin-spin dipolar interactions+ measure distances between the spin labels in the RRERev complexes, EPR spectra were collected at Ϫ140 8C+ These absorption spectra are shown overlapped in Figure 4+ The spectrum for RRE2-Rev is the broadest, followed closely by RRE1-Rev and RRE3-Rev+ At low temperatures at which the molecular motion is completely frozen, the broadening of EPR spectra is exclusively due to dipole-dipole interactions between the two spin labels (Rabenstein & Shin, 1995)+ For labels that are proximal and more interacting, spectra are broader+ Conversely, distant spin labels yield narrower peaks+ Qualitatively, then, it is clear that the distance between labels in the RRE3-Rev complex is greater than that in either the RRE1 or RRE2 complexes+ Quantitatively, the overall spectral broadening, due to the splitting of EPR lines resulting from spin dipolar interactions, depends on the inverse cube of the distance (r ) between the spins+ This is given by the equation 2B ϭ 1+5g e b(3 cos 3 u Ϫ 1)/r 3 where 2B is the splitting due to the spin-spin interactions, g e is the isotropic g value of an electron, b is the electron Bohr magneton, and u is the angle between the interspin vector and the external magnetic field, which, for a frozen molecule, is fixed in time and is isotropically distributed+ The magnitude of B is obtained from a Fourier analysis of a frozen EPR spectrum, a method developed by Rabenstein and Shin (1995)+…”
Section: Epr Spectroscopysupporting
confidence: 65%
“…The resulting distances are given in Figure 5 in black with the modeled distances from two lowest-energy NMR shown in blue and green+ The difference between the numbers in blue and green (Fig+ 5) gives an estimate of the range of distances as determined by NMR+ For RRE1 the nitroxide tip-to-tip distance from the 59 end to Rev position 51 is 14 Å, whereas the modeled NMR distance, C a -P, is 15 Å+ The RRE3-Rev distance, on the other hand, is modeled to be over 40 Å based on NMR data, which is well out of the 25-Å range of EPR (Rabenstein & Shin, 1995;Battiste et al+, 1996)+ Thus, the EPR lineshape of RRE3-Rev at low temperatures (Fig+ 4) is indistinguishable from a singly labeled com-FIGURE 4. Low-temperature EPR absorption spectra of bound and unbound Rev and RRE constructs+ The spectra were collected in a quartz vacuum dewer held at Ϫ140 8C with the modulation amplitude set to 3+2 G+ The broadening of the RRE1 and RRE2 spectra indicates spin-spin interactions+ plexed spectrum+ In the case of RRE2-Rev, the measured tip-to-tip distance is 12 Å and the modeled C a -P based on NOE constraints is between 6 and 10 Å+…”
Section: Epr Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations